Proceedings of the Second Annual Deep Brain Stimulation Think Tank: What's in the Pipeline. (3rd July 2015) - Gunduz, Aysegul; Morita, Hokuto; Rossi, P. Justin; Allen, William L.; Alterman, Ron L.; Bronte-Stewart, Helen; Butson, Christopher R.; Charles, David; Deckers, Sjaak; de Hemptinne, Coralie; DeLong, Mahlon; Dougherty, Darin; et al.
Abstract : The proceedings of the 2nd Annual Deep Brain Stimulation Think Tank summarize the most contemporary clinical, electrophysiological, and computational work on DBS for the treatment of neurological and neuropsychiatric disease and represent the insights of a unique multidisciplinary ensemble of expert neurologists, neurosurgeons, neuropsychologists, psychiatrists, scientists, engineers and members of industry. Presentations and discussions covered a broad range of topics, including advocacy for DBS, improving clinical outcomes, innovations in computational models of DBS, understanding of the neurophysiology of Parkinson's disease (PD) and Tourette syndrome (TS) and evolving sensor and device technologies.